Republic of Moldova : Economic Development Document. (IMF Staff Country Reports; Country Report, 2017)
This Economic Development Document highlights the Moldova 2020 National Development Strategy focus on producing a social and economic impact on various development priorities. Poverty reduction has progressed significantly during the past eight years: the national poverty rate decreased from 26.4 percent in 2008 to 9.6 percent in 2015. Remittances by emigrants and higher agricultural income, salaries, and social benefits were the major drivers of poverty reduction. The means-tested social assistance program had a significant impact. This social aid has proved to be the most efficient social protection against poverty; however, social support programs that are not means tested are ineffective.